2018
DOI: 10.1186/s12886-018-0780-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of refractive errors in Tibetan adolescents

Abstract: BackgroundThe prevalence of adolescent eye disease in remote areas of the Qinghai-Tibet Plateau has rarely been reported. To understand the prevalence of common eye diseases in Tibet, we performed ocular-disease screening on students from primary and secondary schools in Tibet, and compared the prevalence to that in the Central China Plain (referred to here as the “plains area”).MethodsThe refractive status of students was evaluated with a Spot™ vision screener. The test was conducted three or fewer times for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 13 publications
1
25
1
Order By: Relevance
“…The unique conditions of the plateau environment include low air pressure, low oxygen levels, dryness, cold weather, intense solar infrared, and ultraviolet radiation, etc. [ 24 ]. These characteristics are inherently detrimental to human survival since they affect the human body and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique conditions of the plateau environment include low air pressure, low oxygen levels, dryness, cold weather, intense solar infrared, and ultraviolet radiation, etc. [ 24 ]. These characteristics are inherently detrimental to human survival since they affect the human body and lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that living at altitudes above 3000 m can have an impact on the human body [ 22 , 23 ]. As a result, congenital heart disease, hypertension, and other diseases have high morbidity in Tibet and may be influenced by the extreme living environments [ 24 ]. The plateau environment not only impacts the human body but also lifestyles, and thus may also affect PA. Several studies have reported on the growth and development characteristics of children and adolescents in Tibet [ 25 , 26 ], as well as the related situations of eye diseases [ 24 ], rickets/Kaschin-Beck disease [ 27 , 28 ], and nutrition [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The potential influence of ethnic, environmental, lifestyle and genetic susceptibility differences [ 16 ] is still unclear. Qian reported that the prevalence of ocular disease differences in Tibet may relate to more exposure to sunlight and easier schooling [ 29 ] Whether Tibetan children have a higher prevalence of strabismus requires further investigation. Secondly, different age ranges across the different studies may play an important role [ 3 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this probably relates to the status of refraction; the distribution of the cycloplegic SE of esotropia in LCES tend to be hyperopia, which was consistent with the finding that exotropia was associated with astigmatism, myopia and low to moderate hyperopia, while esotropia was associated with hyperopia in a dose-response manner [ 16 , 30 , 31 ]. Qian also found that Tibetan adolescents had a lower prevalence of refractive errors than the plains (central China) area except for hyperopia, and also suggested that the rate of hyperopia in Tibet is higher [ 29 ]. As we show here, in the present LCES study the prevalence of hyperopia was higher at 6.91%.…”
Section: Discussionmentioning
confidence: 99%
“…87.65%, Eastern China) (17) Guangzhou (69.9%, Southern China) (17) Beijing (70.9%, Northern China) (18) Qingdao (52.02%, Eastern China (18), Chongqing (54.9%, Western China), and Tianjin (53.9%, Northern China) (19), but higher than Mangshi (35.9%,Western Rural China) (20) and Tibet 28.51%, Plateau of China(20). (Table 3)(Figure.…”
mentioning
confidence: 99%